Pengaruh Pemicuan Terhadap Angka Bebas Jentik (Abj) Di Kelurahan Rahandouna Kota Kendari - Muhammad Abdul Gafur Tirtayasa Mangidi; Sunarsih Sunarsih; Erwin Azizi Jayadipraja (Al-Sihah : The Public Health Science Journal, 2019)
ABSTRACTWithin the last three years Dengue Hemorrhagic Fever (DHF) is still a problem in Kendari, where almost every year an outbreak of dengue fever in the morbidity and mortality is high enough.  Larva index is one index in seeing the success rate of DHF control programs. Rahandouna is the village with the lowest larva index proportion in Kendari. Participatory method is needed to urge people to participate in the preventive and promotive, such as triggered. This study aims to analyze the effect of triggering against larvae index in Rahandouna. This research is a quasi experiment with control time series design. The population in this study are all the houses in the Rahandouna many as 3,093 houses. Sampling was done by simple random sampling with 39 respondents of each group. Samples were measured before the intervention and then each week for four weeks in each group. The intervention was triggering group and untreated control. Data analysis used independent sample t-test. The results showed a triggering effect on larvae index in the Rahandouna with the statistical test using independent test - sample t-test obtained by value p = 0,012 <0,05. Therefore triggering method is expected to be one of the alternative methods of reduction program morbidity and mortality due to DHF.Keywords: triggering; larva index; dengue hemorrhagic fever